2017
DOI: 10.1111/1751-2980.12458
|View full text |Cite
|
Sign up to set email alerts
|

Split‐dose bowel preparation with polyethylene glycol for colonoscopy performed under propofol sedation. Is there an optimal timing?

Abstract: The consumption of bowel preparation agent within 3-4 h before propofol sedation resulted in a similar RGV and pH as those achieved by more prolonged fasting, with no increased risk of aspiration even in patients perceived to be at high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Similarly, fasting time before adult colonoscopy is being widely reduced due to the popularity of superior split-and large-volume bowel preparations in which the last dose is typically completed 3 hours before the procedure. Such shorter fasting does not increase gastric volume or acidity [75][76][77][78], and does not appear to increase aspiration risk during the associated propofol deep sedation or anaesthesia [75][76][77][78][79].…”
Section: Absent Risk Factorsmentioning
confidence: 97%
“…Similarly, fasting time before adult colonoscopy is being widely reduced due to the popularity of superior split-and large-volume bowel preparations in which the last dose is typically completed 3 hours before the procedure. Such shorter fasting does not increase gastric volume or acidity [75][76][77][78], and does not appear to increase aspiration risk during the associated propofol deep sedation or anaesthesia [75][76][77][78][79].…”
Section: Absent Risk Factorsmentioning
confidence: 97%
“…Similarly, consumption of split-dose bowel prep within 3 to 4 hours of propofol sedation has not shown to increase risk of aspiration. 94…”
Section: Sedation-related Aesmentioning
confidence: 99%
“…However, it is not just endoscopists who have a role in this improvement. For example, even though studies have demonstrated that residual gastric volume is not higher with a split-dose regimen when the last dose of preparation is consumed at least 3 hours before the colonoscopy 23 24 25 26 , in our study, anesthesiological concerns seem to be relevant in hampering the adoption of a split-dose regimen.…”
Section: Discussionmentioning
confidence: 56%